Joining of Incompatible Polymer Combinations by Form Fit Using the Vibration Welding Process - Michael Wolf; Tobias Kleffel; Christoph Leisen; Dietmar Drummer (International Journal of Polymer Science)
The production of components consisting of various polymer types by welding is severely restricted and only possible for bonding compatible materials with melting points in a close range. Several modifications, such as the cross-linking of one joining partner, allow for circumventing the restrictions regarding the melting points but do not help in joining bonding incompatible materials. Investigations of dissimilar material combinations, especially from polymer-metal hybrid structures, show a high potential of connections based on form fits. Within the scope of this paper, the possibility of joining incompatible polymer combinations, such as polyamide 66 and high-density polyethylene, by micro form fit using the vibration welding process is analyzed. For this purpose, the generated bonding strength of the test specimen was determined by shear tests. Furthermore, the undercuts of the generated prestructures and the resulting bond of the test specimen were examined microscopically by computer-tomography. These investigations depict the high potential of joining incompatible polymer combinations by form fit in the vibration welding using prestructuring to generate undercuts.